THE EFFECT OF GOOD CORPORATE GOVERNANCE MECHANISMS ON FINANCIAL PERFORMANCE IN CONVENTIONAL COMMERCIAL BANKS LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2015-2019 - Pandu Rizky Mahendra; Tituk Diah Widajantie (JURNAL ILMIAH EDUNOMIKA, 2021)
The study was conducted to obtain empirical evidence related to the effect of good corporate governance mechanisms on the financial performance of banking companies. The population are banking companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Total population of registered banking companies is 45 companies. This research uses purposive sampling technique. From the total of population, only 25 conventional general banking companies meet the criteria. After that multiplied by the research period of five years, then there are 125 samples in this study. The analysis technique used is regression analysis which is a method of analyzing research hypotheses with the aim of testing the overall presence or absence of the influence of one variable with another variable. Based on the results of the study "The Effect of Good Corporate Governance Mechanisms on Financial Performance in Conventional Commercial Banks Listed in Indonesia Stock Exchange Period 2015-2019 " the following conclusions were obtained: The Board of Directors has an effect on the financial performance (Return On Assets) of Conventional Commercial Banks. The Board of Commissioners does not affect the financial performance (Return On Assets) at Conventional Commercial Banks. The Audit Committee has an effect on financial performance (Return On Assets) at Conventional Commercial Banks. Keywords: good corporate governance, financial performance